(untitled) (Nepal Journal of Health Sciences, 2025)
Introduction: Although the diagnosis of anaemia no longer remains a significant challenge in Nepal due to the availability of diagnostic technologies, even in rural settings, the accurate classification of anaemia however, remains challenging due to a lack of qualified pathologists across the healthcare facilities. Objective: To study the morphological types of anaemia in patients visiting Madan Bhandari Academy of Health Sciences Hetauda Hospital. Methods: Hospital based cross sectional study was used to evaluate anaemia based on morphological characteristics and haematological parameters among patients visiting the hematology lab of Madan Bhandari Academy of Health Sciences, Hetauda Hospital from 2021-05-23 to 2021-12-31. By using MIDAS software 386 patients were recruited. Ethical approval was taken from Nepal Health Research Council. Statistical analysis was performed using SPSS version 16, with categorical variables summarized as frequencies and percentages. Result: The majority of participants were diagnosed with microcytic hypochromic anaemia, with a notable predominance among females. Additionally, the highest proportion of cases was observed in adults aged 45 years and older. Conclusion: A concerning finding was that vulnerable groups, women, adults over 45, and children were significantly affected by microcytic hypochromic anaemia. The high prevalence indicates a considerable burden of likely preventable anaemia, underscoring the urgent need for public health action and government-supported dietary interventions.